Analyzing the Efficiency of E-Assessment of EAP Courses amid COVID-19 in Bangladesh - Nazia Masood; Faheem Hasan Shahed (Celebes Journal of Language Studies, 2022)
In industrialized countries, conducting online classes has been a common phenomenon. However, it became quite challenging to arrange virtual classes for a developing country like Bangladesh during the COVID-19pandemic. Teachers at all levels had to cope with the situation to make a drastic shift from offline to online classes in a short period of time. Although teachers could successfully take virtual classes, concerns about the efficacy of e-assessment remained since assessments must depict the actual scenario of students' learning. This mixed-method study tried to figure out the efficiency of e-assessment of EAP (English for Academic Purposes) courses. To facilitate, 30 students and 4 teachers of privately-run universities in Dhaka virtually took part in this research. The findings reveal that the students could find validity and reliability in the e-assessment, but technical glitches made the e-assessments impractical. On the contrary, teacher participants could only ensure the presence of validity. At the same time, they could apply the concept of zone of proximal development by Vygotsky and comprehensible input hypothesis by Krashen.